Analisis Dampak PDRB Terhadap Kemiskinan Di Provinsi Banten Tahun 2018-2022 - Geri Gerung, Muhammad Buyung; Maryani, Iin; Alfahira, Vira; Nurhasanah, Siti; Azizah, Nur; Desmawan, Deris (Universitas Labuhanbatu, 2023)
If there is any effect between these two variables, the Gross Regional Domestic Product or GRDP and Poverty in Banten Province from 2018 to 2022 must be considered. Among variables studied, the independent variable is GRDP and the dependent variable is poverty. The research methodology used in this study is a quantitative approach based on data from Central Statistics Agency (BPS) and several literature reviews were conducted. The results showed that GRDP has a significant impact on poverty. As the GRDP indicator increases, poverty in Banten decrease.